De la faculté de juger les zones humides - Yves Meinard (Développement Durable et Territoires)
Numerous policies are devoted to protecting wetlands. This is the case in many countries around the world, and more specifically in France, where numerous environmental regulations and policy frameworks focus on wetlands. Using a participating research methodology, this article analyses the features and stakes of expert judgments involved in the implementation of these policies. Although these judgments superficially seem to be entirely technical, they involve a projective, value-laden understanding of the endeavour to conserve wetland. This analysis suggests rethinking the tools used to supervise expertise.